2017
DOI: 10.23910/ijbsm/2017.8.6.1846a
|View full text |Cite
|
Sign up to set email alerts
|

Residual Effect of Nutrient Management Practices in Hybrid Rice under Sri on Growth and Yield of Greengram (Vigna radiata L.) in Rice-greengram Cropping System

Abstract: The field experiments were conducted to study the residual effect of nutrient management practices of kharif rice on growth and yield of rabi greengram was conducted at Krishi Vigyan Kendra, Balasore Odisha during rabi 2013−14 and 2014−15. The experiment was laid out in RBD during the kharif season with 12 treatments replicated thrice and rabi greengram was grown in the residual fertility in the plots without disturbing the layout. The residual effect of different nutrient management prcatices applied to khari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
3
0
0
Order By: Relevance
“…Higher availability of residual nutrients in coconut residues based vermicompost applied to the preceeding crop which slowly released the nutrients and changed the soil environment that might have supplied to the succeeding crops. Similar findings were also observed by [12] and [13].…”
Section: Plant Heightsupporting
confidence: 92%
“…Higher availability of residual nutrients in coconut residues based vermicompost applied to the preceeding crop which slowly released the nutrients and changed the soil environment that might have supplied to the succeeding crops. Similar findings were also observed by [12] and [13].…”
Section: Plant Heightsupporting
confidence: 92%
“…There was non-significant effect of kharif rice varieties on yield components, seed yield, haulm yield and harvest index of succeeding rabi black gram. Present findings with higher yield of succeeding black gram on residual fertility after rice were also in conformity with the findings of Rama Lakshmi et al ( 2012) and Dash et al (2017) where residual effect of organic and inorganic sources of nutrients in rice combinedly showed significantly higher growth, yield attributes and yield of succeeding rabi green gram than sole preceding crop were also reported by Shanwad et al (2010) in maize-bengal gram sequence, Mohanty et al (2014) in rice-green gram sequence and Samant et al (2021 ) in rice groundnut cropping sequence.…”
Section: Yield Components and Yieldsupporting
confidence: 92%
“…Highest number of primary branches per plant and dry matter accumulation (5.70 and 9.28 g plant -1 , respectively) was recorded in treatment with residual effect of nutrient management as rice crop manager which was at par with use of 50% RDF+FYM @ 8 t ha -1 (5.51 and 9.04 g plant -1 , respectively) but significantly higher than 50% RDF+Sesbania green manuring @ 1.5 t ha -1 . Dash et al (2017) also confirmed substantial residual effect resulted from combined use of organic and chemical sources of plant nutrients in kharif hybrid rice on growth attributes and yield of succeeding rabi green gram in ricegreen gram sequence. Similar reports of higher crop growth parameters viz.…”
Section: Growth Attributessupporting
confidence: 52%
“…Treatment T 10 had the longest pods, followed closely by Vermicompost+ FYM and inorganic fertilizers with all levels of fertility registered boldness and sound health of seeds which ultimately resulted in higher seed weight, and these also improved the size of grain by improving the availability of soil nutrients and translocation of manufactured food from source to sink in plant and ultimately increased the yield. A similar result has been reported by Singh et al [16] and Rupa et al [19].…”
Section: Effect Of Inm Treatments On Yield Attributing Parametersupporting
confidence: 91%
“…The combined application of Rhizobium, Vermicompost, FYM, and chemical fertilization to the treatments increased the availability of nutrients over a longer period, which had a beneficial influence on the growth metrics, resulting in higher plant dry matter. Consistent findings are also found by Dash et al [16] and Singh et al [17].…”
Section: Number Of Rhizobium Nodules Plant -1supporting
confidence: 88%